Review of Jeremiah Morelock (Ed.), Critical Theory and Authoritarian Populism (2018). London: University of Westminster Press. - Daniel Sullivan (tripleC: Communication, Capitalism & Critique)
Critical Theory and Authoritarian Populism (2018; University of Westminster Press), edited by Jeremiah Morelock, brings together the work of sociologists, political scientists, historians, and philosophers attempting to revitalise the empirical and theoretical work on antidemocratic trends of the early Frankfurt School, or Institute for Social Research. They do so in the analytic context of contemporary, globally observed ‘authoritarian populist’ movements, in which political (often right-wing) agitators pit a symbolically-constructed national ‘people’ against purported corrupt elites and minority scapegoat groups. The chapters cover wide ground and can be contrasted to some extent in terms of whether they frame the contemporary moment as highly similar to the era of the Great Depression and 1930s Fascism, or emphasise the unique nature of neoliberalism as a historical backdrop. Notable strengths of the volume include Morelock’s systematic introductory overview of early Frankfurt School work, as well as a thematic section on “Digital Authoritarianism” which resurrects the Institute’s tradition of propaganda content analysis for the social media era. Critical Theory and Authoritarian Populism offers a highly comprehensive picture of the current geopolitical nightmare and the conceptual tools for attacking it, and serves as a welcome corrective to several recent simplistic applications of the authoritarianism concept in popular science outlets.